Pediatric Pain Screening Tool: rapid identification of risk in youth with pain complaints. Issue 8 (August 2015) - Simons, Laura E.; Smith, Allison; Ibagon, Camila; Coakley, Rachael; Logan, Deirdre E.; Schechter, Neil; Borsook, David; Hill, Jonathan C.
Abstract : Abstract: Moderate to severe chronic pain is a problem for 1.7 million children, costing 19.5 billion dollars annually in the United States alone. Risk-stratified care is known to improve outcomes in adults with chronic pain. However, no tool exists to stratify youth who present with pain complaints to appropriate interventions. The Pediatric Pain Screening Tool (PPST) presented here assesses prognostic factors associated with adverse outcomes among youth and defines risk groups to inform efficient treatment decision making. Youth (n = 321, ages 8-18, 90.0% Caucasian, 74.8% female) presenting for multidisciplinary pain clinic evaluation at a tertiary care center participated. Of these, 195 (61.1%) participated at 4-month follow-up. Participants completed the 9-item PPST in addition to measures of functional disability, pain catastrophizing, fear of pain, anxiety, and depressive symptoms. Sensitivity and specificity for the PPST ranged from adequate to excellent, with regard to significant disability (78%, 68%) and high emotional distress (81%, 63%). Participants were classified into low- (11%), medium- (32%), and high- (57%) risk groups. Risk groups did not significantly differ by pain diagnosis, location, or duration. Only 2% to 7% of patients who met reference standard case status for disability and emotional distress at 4-month follow-up were classified as low risk at baseline, whereas 71% to 79% of patients who met reference standard case status at follow-up were classified as high risk at baseline. A 9-item screening tool identifying factors associated with adverse outcomes among youth who present with pain complaints seems valid and provides risk stratification that can potentially guide effective pain treatment recommendations in the clinic setting. Abstract : The Pediatric Pain Screening Tool is the first screening measure to identify the level of risk for poor pain-related outcomes in youth with pain complaints.